High rates of sexual assault kit submission and the important role of place. (March 2020) - Shaw, Jessica; Coates, Victoria; Janulis, Patrick
Highlights: Ninety percent of sexual assault kits were submitted to the crime lab for analysis. Victim, assault, and case factors played little role in predicting kit submission. Submission rates varied significantly between different cities. State and organizational culture, policy, and practice are critically important.